The effect of rainfall runoff on phase partition of palladium in receiving water bodies and the underlying influential mechanism. (January 2022) - Ding, Fangfang; Liu, Yuyan; Zhang, Lan; Ji, Caiye; Wu, Dan; Wang, Lin; Liu, Haofeng
Abstract: The influx of rainfall runoff intensifies phase partition of the pollutant in receiving water bodies, and the phase partition plays an important role in the speciation transformation and spatial partition of pollutants. In this study, the Meishe River on Hainan Island, China, was adopted as the research area, and palladium (Pd) was selected as the target pollutant. The purpose of this study was to explore phase partition of Pd in receiving water bodies and the underlying influential mechanism. The partition coefficients (Kd s) of Pd between water and suspended particulate matter in receiving water bodies and rainfall runoff were 0.74 (0.1 × 10 −2 - 8.75) and 2.74 (0.5 × 10 −2 - 15.70), respectively. These results indicated that Pd dominated the dissolved phase in the receiving water bodies and that Pd dominated the particulate phase in rainfall runoff. Variations in the Kd value of Pd in the receiving water bodies were relatively smooth over time during the precipitation events in May and June. There were no significant differences in phase partition of Pd between the receiving water bodies and rainfall runoff. The Kd value for Pd in the receiving water bodies showed a fluctuating upward trend over time during the precipitation events in August, and the difference in Kd values of Pd between the receiving water bodies and the rainfall runoff were large. Variations in the Kd value of Pd among sections of the receiving water bodies could be roughly divided into two categories, namely, U and inverted-U types. After rainfall runoff converged for 20–25 min, the Pd phase transitions were more frequent within 7 m downstream of the outfall. The Kd value of Pd in the receiving water bodies was correlated with pH, Eh, and total suspended solid (TSS), and the correlation coefficients were 0.52, −0.57, and 0.84, respectively (p < 0.05). Compared with rainfall runoff, pH, Eh, TSS had less influence on phase partition of Pd in receiving water bodies. This might be attributed to the dilution effect of natural water and the unique dynamic mechanism of rivers. Highlights: Pd dominated the dissolved phase in the receiving water bodies. Phase transfer of Pd was more frequent within 7 m downstream of the outfall. The Kd of Pd in receiving water bodies was closely related to rainfall characteristics. Rainfall runoff had larger influence on phase partition of Pd in the receiving water bodies.